You can put this solution on YOUR website!
y = -2x^2 + 8x - 6 [Eliminate the lead coefficient by dividing all terms by -2]
-2x^2/-2 + 8x/-2 - 6/-2=0 [Set the equation equal to zero]
x^2 -4x +3-3=0=-3 [Subtract the "C" term from both sides of the eqaution]
x^2 -4x =-3 [Divide the "B" term by 2 and raise it to the 2nd power. Add the result to both sides of the equation]
x^2 -4x +(4/2)^2=-3+(4/2)^2
x^2 -4x +2^2=-3+2^2 [Simplify]
x^2 -4x +2^2=-3+4
(x-2)(x-2)=1 [Factor the left side]
sqrt(x-2)^2=sqrt(1) [Take the square root of both sides]
x-2=+-1 [Solve for x]
Check by plugging the values of x back into the original equation.